Assessment of Education Quality Assurance Conditions During Public Accreditation of Educational Organization - T. A. Pavlova; A. Yu. Paromov (Управленческое консультирование)
The article proposes to evaluate the conditions of educational activities, which ensure the quality of education, during public accreditation of an educational organization. The approach is based on the use of the mechanism of external independent evaluation, conducted by a public organization, to determine the level of an educational organization in order to promote consistent improvement in the quality of the processes of providing and implementing educational activities. A number of indicators that can be expressed quantitatively are proposed. The work of the educational organization to ensure the quality of education in this case can be evaluated on the basis of the proposed indicators.